Purity of hydrogen released from the Liquid Organic Hydrogen Carrier compound perhydro dibenzyltoluene by catalytic dehydrogenation. (1st January 2020) - Bulgarin, A.; Jorschick, H.; Preuster, P.; Bösmann, A.; Wasserscheid, P.
Abstract: While Liquid Organic Hydrogen Carrier (LOHC) systems offer a very promising way of infrastructure-compatible storage and transport of hydrogen, the hydrogen quality released from charged LOHC compounds by catalytic dehydrogenation has been a surprisingly rarely discussed topic to date. This contribution deals, therefore, with a detailed analysis of the hydrogen purity released from the hydrogen-rich Liquid Organic Hydrogen Carrier compound perhydro dibenzyltoluene (H18-DBT). We demonstrate, that high purity hydrogen (>99.999%) with carbon monoxide levels below 0.2 ppmv can be obtained from the dehydrogenation of H18-DBT if the applied H18-DBT had been carefully pre-dried and pre-purified prior to the dehydrogenation experiment. Indeed, the largest part of relevant impurities to comply with the hydrogen quality standard for fuel cells in road vehicles (ISO 14687-2) was found to originate from water and oxygenate impurities present in the applied, technical LOHC qualities. Graphical abstract: Image 1 Highlights: Impurities in the technical LOHC account for most impurities in the released H2 . Water in perhydro dibenzyltoluene (H18-DBT) is a source of CO impurities. Oxygenate impurities in H18-DBT are another source of CO. The use of pre-purified H18-DBT leads to higher productivity in H2 release. Purified H18-DBT releases H2 of excellent quality, CO levels are below 0.2 ppmv.